Concrete durability : a practical guide to the design of durable concrete structures - Soutsos, Marios (Thomas Telford, 2010)
This is a comprehensive, practical guide for engineers involved in designing concrete structures of all types. It combines a thorough but accessible exposition of the principles of durable concrete design with a practical, hands-on approach to its application in construction projects.
Keywords: Concrete -- Testing.; Concrete -- Deterioration.; elektronické knihy; electronic books